2022
DOI: 10.26656/fr.2017.6(1).084
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of date seed powder (Phoenix dactylifera L.) for tenderizing properties of different types of meat

Abstract: Recently, date (Phoenix dactylifera L.) seeds have gained much popularity due to their vast applications that benefit people and the environment, elevated with plenty of research on food product formulation, cosmetics, and medicinal supplements. Date seeds constitute 10-15% of the date fruit weight. Although date seeds are considered waste products, however, they contain many valuable substances such as carbohydrates, oil, dietary fibre, protein, bio-active polyphenol, tannin and natural antioxidants. Thus, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…24 Condensed tannins form hydrogen bonds with meat proteins, acting as antioxidants and preserving meat tenderness. 139 This concept was applied by Nor et al (2022) 140 in a study on the tenderizing effect of date seed powder on lamb and beef. The addition of date seed powder resulted in a reduction in the major textural properties of marinated lamb and beef samples compared to the control, with a comparable decrease in water holding capacity and cooking loss in meat samples with increased date seed powder.…”
Section: Application Of Date By-products In Food Applicationsmentioning
confidence: 99%
“…24 Condensed tannins form hydrogen bonds with meat proteins, acting as antioxidants and preserving meat tenderness. 139 This concept was applied by Nor et al (2022) 140 in a study on the tenderizing effect of date seed powder on lamb and beef. The addition of date seed powder resulted in a reduction in the major textural properties of marinated lamb and beef samples compared to the control, with a comparable decrease in water holding capacity and cooking loss in meat samples with increased date seed powder.…”
Section: Application Of Date By-products In Food Applicationsmentioning
confidence: 99%
“…were not detected in treated samples. Similarly, Nor et al [ 59 ] evaluated the tendering effect of date seed powder towards beef and lamb meat. These authors found that textural properties such as hardness, springiness, chewiness, and gumminess decreased between the different amounts of seed powder used in marinated beef and lamb with respect to control.…”
Section: Application Of Date Fruits Products and Co-products In Foodsmentioning
confidence: 99%